2017
DOI: 10.3832/ifor1999-009
|View full text |Cite
|
Sign up to set email alerts
|

A quick screening to assess the phytoextraction potential of cadmium and copper in Quercus pubescens plantlets

Abstract: The relevance of the environmental pollution by heavy metals warrants the necessity to develop and assess more efficient plant-based technologies. This study was conducted to evaluate a quick screening approach in order to investigate the cadmium (Cd) and copper (Cu) phytoextraction potential of Quercus pubescens in a micro-propagation system. Increasing concentrations of Cd (0, 5, 50, and 250 µM) and Cu (0, 5, 50, 250 and 500 µM) were separately applied to evaluate the effect of metals on their absorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In comparison with commercially available media, the three novel Qd basal salt media had substantially greater amounts of Cu and lower Fe and Zn concentrations ( Table 2 ). Interestingly, a study aimed at evaluating downy oak ( Q. pubescens ) for phytoremediation of soil contaminated with Cu or Cd found that the addition of 5 µM Cu increased growth, although higher concentrations decreased it [ 26 ]. Both DKW and MS contained greater quantities of total N than all three Qd salts or WPM, which may have been one of the major factors in why either MS or DKW had much greater necrosis than the other four.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with commercially available media, the three novel Qd basal salt media had substantially greater amounts of Cu and lower Fe and Zn concentrations ( Table 2 ). Interestingly, a study aimed at evaluating downy oak ( Q. pubescens ) for phytoremediation of soil contaminated with Cu or Cd found that the addition of 5 µM Cu increased growth, although higher concentrations decreased it [ 26 ]. Both DKW and MS contained greater quantities of total N than all three Qd salts or WPM, which may have been one of the major factors in why either MS or DKW had much greater necrosis than the other four.…”
Section: Resultsmentioning
confidence: 99%